Orobanche dagestanica (Orobanchaceae): a new species from the Greater Caucasus - Piwowarczyk, Renata; Sánchez Pedraja, Óscar; Fateryga, Alexander V.; Svirin, Sergey A.; Murtazaliev, Ramazan A. (Phytotaxa, 2024)
A new, probably endemic species, Orobanche dagestanica is described from Dagestan in Russia (the Greater Caucasus). The species grows in alpine shale scree slopes, and is a parasite of the roots of species from the genus Lophiolepis (Asteraceae). Based on morphological and phylogenetic data, the newly-described species belongs to Orobanche subsect. Curvatae, and specifically to O. ser. Krylowianae, however it is distinct from all other taxa in this group. A detailed description, diagnosis, illustrations, a comparison with related species, as well as phylogenetic analysis are provided.